Ketentuan Tugas Akhir Artikel Ilmiah Pengganti Skripsi: Studi Kebijakan pada Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Hidayatul Fikra; Susanti Vera; Fitriani Fitriani (Gunung Djati Conference Series, 2024)
This research aims to analyze the final assignment policy for scientific articles. This research uses a qualitative approach by applying policy analysis methods. The results of the research and discussion show that the final assignment policy is basically an option for students to obtain a bachelor's degree, although it is recognized that the publication of scientific articles has added value as an undergraduate achievement and pride in higher education. It is called an achievement because undergraduates have traces of scientific publications in primary sources of scientific journals and the pride of higher education because it supports the performance of scientific publications. This research concludes that the final scientific article assignment policy has a significant impact on the future by providing challenges for students from an early age to practice improving their scientific article writing skills during college.